Penerapan Green Supply Chain Management Untuk Peningkatan Kinerja Keuangan Perusahaan - Puryono, Daniel Alfa; Mustafid, Mustafid; Jie, Ferry (Universitas Diponegoro, 2016)
In this research the assessment of the processes green supply chain management for corporate financial performance improvement. This research was based on the company goal to achieve profit by lowering the risk and environmental impact while improving the ecological efficiency by implementing green supply chain management in order to improve the company's financial performance.The method used in this research is a Green Supply Chain Management (GSCM). The management process of the company was done with by giving weight to the indicators of the green supply chain and measuring supply chain performance by using AHP method. Then compared with the acquired real weight of the Green SCOR model. While to measuring the financial performance of the company to know the position of the company by using ROA and EVA calculation that exist in the methods of Du Pont Ratio Analysis.The results of this research is a decision system information which is capable of linking green supply chain performance with the company's financial performance. The results of the analysis indicated that the supplying, making, delivering and returning are very sustainable. The assessment result shows 87.3% of companies have increased the company's financial and 12.7% companiesâ€™ efï¬ciency. This information system can be developed to assist the manager in the company's decision-making started from the sustainable design.Â This research method can be developed to assess the extent of each indicator of the supply chain performance related to the financial strategies.